Effectiveness of works procurement contract management in achieving value for money: A case study of College of Business Education – Dar es Salaam Campus - Mnango, Hassan I. (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfillment of the Requirement for the Award of Master of Science in Procurement and Supply Chain Management (Msc. PSCM) of Mzumbe University, 2017